AN EXAMINATION OF CUSTOMER SATISFACTION TOWARD ONLINE FOOD SHOPPING DURING COVID-19 PANDEMIC - Wahyuningsih, Wahyuningsih; Nasution, Hanny; Roostika, Ratna; Yeni, Yulia Hendri (Jurnal Aplikasi Manajemen, 2022)
Customer satisfaction has been considered a key strategic indicator to enhance marketing performance. This study was conducted to compare the satisfaction level of consumers toward online food shopping based on generational differences. The data were collected from consumers who purchase food from the restaurant using the online application across Indonesia. The cross-sectional data were collected utilizing an online questionnaire using Google online application. A total of 445 responses were found to be valid. Descriptive statistics analysis and independent sample T-test were employed to describe behavior in purchasing food online and the difference in customer satisfaction perceived by two generational cohorts. The results show that Gen Y and Gen Z have a significantly different levels of satisfaction. Gen Y feels a higher level of satisfaction than Gen Z. The managerial implications for restaurant managers and service providers are offered. Future research might investigate customer satisfaction for other generational cohorts, for instance, Baby Boomers, generation X, and others. In addition, future research might be conducted for different cultural backgrounds by adding other variables (eWOM, loyalty, marketing performance) resulting from customer satisfaction.